PENGARUH GOOD CORPORATE GOVERNANCE, COMPANY SIZE, CAPITAL STRUCTURE DAN LEVERAGE TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019 – 2022 - Muwafiq, Ahmad; Edi Purnomo, Djauhar; Usamah, U; Ainur rachmani, Ferlinda (Neraca, 2023)
This study aims to determine the effect of Good Corporate Governance, Company Size, Capital Structure and Leverage on financial performance at LQ45 companies registered on Indonesian Stock Exchange in 2019 – 2022. In this case, good corporate governance measured by Independent Board of Commissioners and Institutional Ownerships, company size measured using by In (asset total), capital structure measured using long term debt to equity ratio (LDER), and leverage measured by debt to assets ratio (DAR). The population is the companies listed in LQ45 index during 2019-2022; 64 companies. 27 companies were taken as the samples using purposive sampling technique. It uses multiple linear regression analysis techniques. The result stated partially Independent Board of Commissioners, Company Size, Capital Structure, and Leverage have significantly affected on the financial performance. Otherwise, Institutional Ownership has no effect on it. Simultaneously, Board of Commissioners, Company Size, Capital Structure, and Leverage have significantly affected on the financial performance of the companies LQ45 index registered on the Indonesian Stock Exchange.   REFERENSI Azzahra, A. S., Aset, L. T., & Ratio, L. (2019). Pengaruh Firm Size Dan Leverage Ratio Terhadap Kinerja Keuangan Pada Perusahaan Pertambangan. 9(April), 13–20. Cindyana, W. (2020). Pengaruh Kepemilikan Institusional, Kepemilikan Manajerial, Dewan Komisaris Dan Komisaris Independen Terhadap Kinerja Perusahaan Pada Sektor Industri Barang Konsumsi (Vol. 21, Issue 1). Dewi, A. (2022). Dampak Covid 19 Terhadap Kinerja Keuangan Perusahaan Sub Sektor Otomotif Dan Elektronika Yang Terdaftar Di Bursa Efek Indonesia. 2(2), 1099–1114. http://jurnaltsm.id/index.php/EJATSM Emirzon, J. (2006). Prinsip-Prinsip Good Corporate Governance Pada Perusahaan di Indonesia. Jurnal Manajemen & Bisnis Sriwijaya, 4(8). Fharaswati, M., Hardiyanto, A. T., & Lestari, R. M. E. (2021). Pengaruh Good Corporate Governance Terhadap Kinerja Keuangan Perusahaan Pada Perusahaan Sub Sektor Property Dan Real Estate Yang Terdaftar Di Bursa Efek Indonesia Periode 2014-2018. 8, 1. Fitriani, Y. (2021). Pengaruh good corporate governance dan ukuran perusahaan terhadap kinerja keuangan perusahaan subsektor perbankan yang terdaftar di BEI. 18(4), 703–712. Hansen, V., & Juniarti. (2014). Pengaruh Family Control, Size, Sales Growth, dan Leverage terhadap Profitabilitas dan Nilai Perusahaan. Journal Business Acounting Review, 2(1), 121–130. Ikatan Akuntansi Indonesia. (2012). Standar Akuntansi Keuangan. Salemba Empat. Jensen, M. C., & Meckling, W. H. (1976). Theory of the firm: Managerial behavior, agency costs and ownership structure. Journal of Financial Economics, 3(4), 305–360. https://doi.org/10.1016/0304-405X(76)90026-X Kasmir. (2017). Analisis Laporan Keuangan. Raja Grafindo Persada. Kho, S. (2020). Pengaruh Good Corporate Governance Dan Ukuran Perusahaan Terhadap Kinerja Perusahaan Yang Terdaftar Di Bursa Efek Indonesia. Universitas Putera Batam. KNKG. (2006). Pedoman Umum Good Corporate Governance Indonesia. Komite Nasional Kebijakan Governance (KNKG). Leatemia, E. M., Mangantar, M., Rogi, M. H., Ekonomi, F., Manajemen, J., & Ratulangi, U. S. (2019). Pengaruh Corporate Governance Terhadap Kinerja Keuangan Pada Perusahaan Textile Dan Garmen Yang Terdaftar Di Bursa Efek Indonesia Periode 2013-2017 The Effect Of Corporate Governance On Financial Performance In Textile And Garment Companies Listed On The . 7(3), 4339–4348. Liando, J. S. (2021). Analisis Pengaruh Struktur Modal Terhadap Kinerja Keuangan Perusahaan Manufaktur Sub Sektor Pangan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Di Bei Tahun 2015-2019. Jurnal Indonesia Sosial Teknologi, 14(1), 1–13. https://doi.org/https://doi.org/10.59141/jist.v2i01.71 Ningsih, D. A., & Wuryani, E. (2021). Kepemilikan Institusional, Leverage Dan Ukuran Perusahaan Terhadap Kinerja Keuangan. Jurnal Ilmu Manajemen Volume, 9(2), 18–23. Nurhayati, S. A., & Wijayanti, A. (2022). Pengaruh kepemilikan institusional, likuiditas, dan leverage terhadap profitabilitas. 18(2), 360–368. https://doi.org/10.29264/jinv.v18i2.10616 Nusah, S., & Pondaag, J. J. (2022). Pengaruh Struktur Modal, Good Corporate Governance dan Ukuran Perusahaan Terhadap Kinerja Keuangan Pada Perusahaan yang Terdaftar di Indeks Sri-Kehati. 10(4), 1169–1180. Rahayu, D. P. (2019). Pengaruh Ukuran Perusahaan, Struktur Modal, Dan Likuiditas Terhadap Kinerja Keuanganpada Perusahaan Makanan Dan Minuman …. Jurnal Akuntansi Dan Keuangan Kontemporer …, 2(1), 121–134. Rahman, M. A. (2020). Pengaruh Struktur Modal Dan Pertumbuhan Aset Terhadap Kinerja Keuangan Perusahaan Yang Terdaftar Dalam Jakarta Islamic Index. 3(1), 55–68. Rahmawati. (2021). Pengaruh Good Corporate Governance (GCG) Terhadap Kinerja Keuangan Pada Perusahaan BUMN Yang Terdaftar di BEI. 14(1), 1–13. Ramadhan, A. (2019). Pengaruh Utang Perusahaan terhadap Kinerja Keuangan (Studi Empiris Perusahaan Yang Terdaftar Di Jakarta Islamic Indeks). Jurnal Ilmiah MEA, 3(2), 16–27. https://doi.org/10.31955/mea.vol3.iss2.pp Ramadhani, A. F., & Siddi, P. (2022). Pengaruh good corporate governance terhadap kinerja keuangan perusahaan badan usaha milik negara ( BUMN ) The effect of good corporate governance on the financial performance of state- owned enterprises ( BUMN ). Journal.Feb.Unmui, 24(1), 204–212. Riyanto, B. (2010). Dasar-dasar pembelanjaan perusahaan. BPFE Yogyakarta. Saifi, M. (2019). Pengaruh Corporate Governance dan Struktur Kepemilikan Terhadap Kinerja Keuangan Perusahaan. Profit, 13(02), 1–11. https://doi.org/10.21776/ub.profit.2019.013.02.1 Sari, N., & Wi, P. (2022). Pengaruh leverage, ukuran perusahaan, struktur modal dan profitabilitas terhadap kinerja keuangan perusahaan. Jurnal Akuntansi, 1(3), 1–8. Sari, T. diah, Titisari, K. H., & Nurlaela, S. (2020). Pengaruh Kepemilikan Manajerial, Komite Audit, Leverage Dan Ukuran Perusahaan Terhadap Kinerja Keuangan. Upajiwa Dewantara, 4(1), 15–26. https://doi.org/10.26460/mmud.v4i1.6328 Sariantono, N. E., & Mahyuni, L. P. (2019). Apakah Good Corporate Governance Dan Corporate Social Responsibility Berpengaruh Terhadap Profitabilitas Perusahaan LQ45? Jurnal Ilmiah Akuntansi Dan Bisnis, 4(1), 14. https://doi.org/10.38043/jiab.v4i1.2145 Sartono, A. (2010). Manajemen Keuangan Teori dan Aplikasi. BPFE. Setyaningsih, V. D., & Aufa, M. (2022). Pengaruh Ukuran Perusahaan, Kepemilikan Manajerial, Dan Komisaris Independen Terhadap Kinerja Keuangan Perusahaan. Jurnal Ilmu Manajemen Retail (JIMAT), 3(1), 15–24. www.cnbcindonesia.com. (2020). Bos BEI Buka-bukaan soal Kondisi Bursa RI, Transaksi Drop 24%. Cnbcindonesia.Com. https://www.cnbcindonesia.com/market/20200424104933-17-154146/bos-bei-buka-bukaan-soal-kondisi-bursa-ri-transaksi-drop-24 Suyono, E., Yarram, S. R., & Riswan, R. (2017). Capital structure, corporate performance, and life cycle: Evidence from Indonesia. Corporate Ownership & Control. Risgiyanti, R., & Hidayah, R. (2020). The role of workplace spirituality in reducing the negative impact of organizational cynicism on job performance. Jurnal Aplikasi Manajemen, 18(4), 692-703. Lutfiani, A. P., & Hidayah, R. (2022). ESG Performance and Ownership Structure on Cost of Capital and Research & Development Investment. Fokus Bisnis Media Pengkajian Manajemen dan Akuntansi, 21(1), 25-42. Riswan, R., & Suyono, E. (2016). Corporate diversification: Destroying or increasing firm value? Empirical evidence from Indonesia. Corporate Ownership & Control. 14 (4). Azzahra, M., Yohani, Y., & Fatah, K. (2023). ANALISIS DAMPAK SEBELUM DAN DI SAAT PANDEMI COVID-19 TERHADAP HARGA SAHAM DAN LABA PERUSAHAAN SUB SEKTOR TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA. Jurnal Akuntansi STIE Muhammadiyah Palopo, 9(1), 1-14.